2009
DOI: 10.1348/135532508x342919
|View full text |Cite
|
Sign up to set email alerts
|

A test of methodology intended to assist detection of aggressive offence paralleling behaviour within secure settings

Abstract: UKPurpose. Treatments and risk assessments determined by the offence paralleling behaviour (OPB) framework appear to have found a place in practice well ahead of empirical support and conceptual clarity. Although the framework is intuitively appealing its inappropriate use may have profound negative implications for patients. Incapacitation and unnecessary treatments may be demanded when observed behaviours are interpreted as evidence of persistent pathology related to previous patterns of criminal offending. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…It has been suggested that the complexity of the definition may have contributed to the paucity of methodologies developed for systematically monitoring OPBs (Mann, Thornton, Wakama, Dyson, & Atkinson, 2010, p. 126), and has led to fears that the theory of OPB may be misapplied (Jones et al , 2010, p. 318). Concern about conceptual clarity of OPBs has led to further clinically‐based examination of the index offence and subsequent hospital behaviour (Daffern, Howells, Mannion, & Tonkin, 2009). The Daffern et al (2009) study concluded that, although results were supportive of OPBs, there were also significant dissimilarities between index offence behaviours and behaviours in hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the complexity of the definition may have contributed to the paucity of methodologies developed for systematically monitoring OPBs (Mann, Thornton, Wakama, Dyson, & Atkinson, 2010, p. 126), and has led to fears that the theory of OPB may be misapplied (Jones et al , 2010, p. 318). Concern about conceptual clarity of OPBs has led to further clinically‐based examination of the index offence and subsequent hospital behaviour (Daffern, Howells, Mannion, & Tonkin, 2009). The Daffern et al (2009) study concluded that, although results were supportive of OPBs, there were also significant dissimilarities between index offence behaviours and behaviours in hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Concern about conceptual clarity of OPBs has led to further clinically‐based examination of the index offence and subsequent hospital behaviour (Daffern, Howells, Mannion, & Tonkin, 2009). The Daffern et al (2009) study concluded that, although results were supportive of OPBs, there were also significant dissimilarities between index offence behaviours and behaviours in hospital. Daffern (2010, p. 107) has suggested that much more stringent testing, paying particular attention to issues of reliability and validity, is required of similarities between behaviours inside and outside of institutions, before being applied clinically (Daffern, 2010, p. 110).…”
Section: Introductionmentioning
confidence: 99%
“…For example Daffern et al . () classified patients' aggression using similar categories to those outlined above, to compare similarity between patient's index offence and in‐patient aggressive behaviours. However, this study used different methods to categorize information (e.g., the Behaviour Cycle Logs, a structured document designed to encourage patients to reflect on their behaviours on the wards and to gather more information about the behaviour).…”
Section: Methodsmentioning
confidence: 99%
“…OPB is a relatively new concept that remains in its developmental stage. There have however been several studies which have tested the OPBs concept in clinical settings (Daffern, Ferguson, Ogloff, Thomson, & Howells, ; Daffern, Howells, Stacey, Hogue, & Mooney, ; Daffern, Howells, Mannion, & Tonkin, ). This research has established that there is often some similarity between in‐patient aggressive behaviours and patients' index offences (Daffern et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation